Gas release as a short term instrument to foster competition (2008)
This paper develops a simple model for examining the gas-release programs as the unique tool to improve the performance of imperfectly competitive natural gas markets. We study the «artificial» duopoly effect created by first the incumbent and then by a regulator who introduces a gas-release program under both a partial and a global budget-balance constraint imposed on the incumbent. Calibration and simulation techniques are used to compare these scenarios under different assumptions on the way regulation is conducted. © Presses de Sciences Po.